(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Laboratory experiments were conducted to evaluate thelarvicidal activity of ethanol extracts from the leaves of three plantspecies: Ricinus communis L. (castor plant), Vinca rosea L. (vinca) andLantana camara L. (lantana). Each of three extracts was used at fiverates; namely, 250, 500, 1000, 2000 and 3000 ppm, against the 3rd instarlarvae of Culex quinquefasciatus SAY. Larval mortality percentages wererecorded 24 hours after treatment. The larvicidal effect of each extractwas compared with the standard larvicide temephos (Abate® ). The threetested extracts showed larvicidal effects at all rates. Castor extract had thegreatest larvicidal effect with the lowest LC 50 (323.0 ppm), followed byvinca and lantana extracts. These results suggest that the leaf extracts ofthe three plant species should be considered as promising larvicidesagainst Cx. quinquefasciatus larvae